Now That Was A Riot!: Social Control in Felonious Times. Issue 1 (2nd January 2020) - Loadenthal, Michael
ABSTRACT: In early 2017, dozens of US states introduced legislation designed to further criminalize confrontational protest tactics through expanding the scope of felony prosecutions and summoning the specter of the "riot" to depoliticize political action; indelibly linking it to criminal violence. This shift towards felonies and rioters took the form of legislation, intelligence reports, prosecutions, and rhetorical attempts at nearly every level of government. Demonstrations and campaigns were recast as felonious conspiracies, and the participants, rioters . In doing so, demonstrators were denied legibility as political actors, and instead held up in courts and newspapers as anti-social, irrational, and unruly criminal mobs. These legalistic, rhetorical, and strategic maneuvers can be critically interpreted through a mixed methodological approach embedded within Discourse Analysis and Autoethnography, and interpreted through a genealogical, social control framework. Through a close reading of these rhetorical shifts and their implications for policing and political repression, social movements adopting revolutionary nonviolence can increase resiliency through focusing on creating power, not simply challenging it.